PENGARUH PEMBERIAN ARANG SEKAM PADI DAN TRICHOKOMPOS JERAMI PADI TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays saccharata Sturt) DI LAHAN GAMBUT - Nelvila, Olva; Silvina, Fetmi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine theinteraction effect ofrice husk charcoal and rice straw trichocompost and get the best dosage combination for growth and yield of sweet corn in peatlands. This research was conducted on December 2015 until March 2016. This research used a factorial Randomized Block Design with          3 replications.The first factor was rice husk charcoal (0, 3, 6 kg/plot), and the second factor was rice straw trichocompost (0, 3, 6, 9 kg/plot). Data were analyzed using anova and Duncan's multiple range test at the 5 % level. The results showed that the addition of rice husk charcoal and rice straw trichocompost influenced the growth and production of sweet corn. Rice husk charcoal 3 ̶ 6 kg/plot(5 ̶ 10 ton/ha) and trichocompost of rice straw 9 kg/plot (15 ton/ha) were the best dosage to the growth and yield of sweet corn in peatlands. Keywords: Sweet Corn, Peat, Rice Husk Charcoal, Rice Straw Trichocompost